2009
DOI: 10.1038/bmt.2009.326
|View full text |Cite
|
Sign up to set email alerts
|

Human herpes virus 6 infection is a hallmark of cord blood transplant in adults and may participate to delayed engraftment: a comparison with matched unrelated donors as stem cell source

Abstract: Occurrence of CMV, EBV and human herpes virus 6 (HHV6) infections and immune reconstitution were compared in 15 adult patients receiving a cord blood transplantation (CBT) and 40 patients who received an allogeneic transplantation from a matched unrelated donor (MUD). Herpes virus DNA quantifications in the blood (459 samples) were performed before and then monthly up to 9 months after transplant and the main lymphocytes populations were counted at 3, 6 and 9 months. Incidence of HHV6 infection was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
77
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 43 publications
10
77
3
Order By: Relevance
“…[41][42][43][44] Interestingly, a higher expression of CD46 is observed on the surface of untreated CB cells compared with G-CSF-mobilized hematopoietic progenitor cells used in HSCT, which may contribute to the increased prevalence of post-CBT HHV-6 reactivation. 10,45,46 However, several lines of evidence suggest that other cellular factors in addition to CD46 are crucial to the establishment of active HHV-6 infection in vivo. 41 Ogata et al 47 demonstrated that serum IL-6 levels increase dramatically in patients experiencing HHV-6 reactivation, showing a correlation between high levels of IL-6 in serum and CSF and the development of encephalitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[41][42][43][44] Interestingly, a higher expression of CD46 is observed on the surface of untreated CB cells compared with G-CSF-mobilized hematopoietic progenitor cells used in HSCT, which may contribute to the increased prevalence of post-CBT HHV-6 reactivation. 10,45,46 However, several lines of evidence suggest that other cellular factors in addition to CD46 are crucial to the establishment of active HHV-6 infection in vivo. 41 Ogata et al 47 demonstrated that serum IL-6 levels increase dramatically in patients experiencing HHV-6 reactivation, showing a correlation between high levels of IL-6 in serum and CSF and the development of encephalitis.…”
Section: Discussionmentioning
confidence: 99%
“…Forest plots were built using STATA's user-developed 'metan' procedure. 33 63 Mixed 4500 copies per mL detected in whole blood 68.5% (37/54) 32.1% (9/28) Ishiyama et al 66 Adult 4100 copies per mL detected in plasma 80% (12/15) 0% (0/5) a Chevallier et al 10 Adult Defined by either one positive PCR test of 41000 copies per mL detected in whole blood or two consecutive positive PCR tests of 4100 copies per mL detected in whole blood 80% (12/15) 42.5% (17/40)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has to be a subject of further research. Up to now, several risk factors for delayed engraftment have been identified, including HHV6 infection, 44 gene polymorphisms, 45 splenomegaly 46,47 and others. 3,[44][45][46][47][48][49][50][51][52][53] The current results underline that further investigation of this topic Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…CMV, EBV, adenovirus and Human Herpes Virus 6 were routinely screened by quantitative PCR. 13 EBV monitoring and therapy During the first 6 months after UCBT and in patients treated for GVHD, weekly DNA-PCR screening was performed in the peripheral blood for EBV reactivation and all patients were clinically monitored for clinical features attributable to EBV. After the first 6 months, if no reactivation occurred, the screening for EBV was regularly performed (usually monthly) and whenever clinically relevant, until full immune reconstitution of the patient was achieved.…”
Section: Gvhd Prophylaxis and Treatmentmentioning
confidence: 99%